DOES LEADERSHIP MATTER? STUDY OF LEADERSHIP STYLE, JOB PERFORMANCE AND JOB SATISFACTION - Chang, Heidi (Poslovna ekonomija, 2018)
Leadership style plays an important role in organization because a good leader can influence their followers to achieve the organization goals. However, each leader has their own characteristic and style in coordinate their subordinates. This study aims to explore how leadership styles affect job satisfaction and job performance. On-line questionnaire was adopted for data collection. There are 200 participants who work for the top-20 companies in Indonesia. The results indicated that the leadership style is significantly and positively correlated to job satisfaction and job performance. Furthermore, this study found that job satisfaction has a mediating effect on the relationship between leadership style and job performance.